From Text to Context: Ricoeur’s Hermeneutical Analysis of the Narrative of Power in Indonesian Political Discourse - Muhammad Idham Kholid (Manunggal Halim Jaya, 2026)
This study examines how narratives of power are produced, configured, and reinterpreted in Indonesian political discourse, utilizing Paul Ricoeur's narrative hermeneutics. In contemporary politics, actors rely on storytelling as a legitimation strategy, exercising power through symbolic constructions. Applying Ricoeur's threefold mimesis, this research analyzes political speeches and media discourse as texts shaping collective experience. The analysis reveals that narratives of power are built upon stable patterns such as morality, nationalism, and stability. In mimesis I, oligarchic dominance and leader personalization serve as pre-understandings for political stories. Mimesis II demonstrates how political actors weave metaphors to produce coherent leadership narratives. Finally, in mimesis III, audiences refigure these narratives based on their experiential horizons within digital spaces. The study concludes that Ricoeur's hermeneutics provides a powerful critical tool for examining power reproduction and legitimacy, offering a framework for ideological critique and interpretation-based political studies.